Effect of Ergonomic Exercises in Modifying Sirtuin1 Gene Expression in Obese Down Syndrome Patients - Hala M. Zeidan, Mohamed Maher Ahmed, Adel F. Hashish, Hend Rashad, Ehab R. Abdol Raouf (Journal of Applied Pharmaceutical Science, 2017)
The current study was conducted to investigate the effect of ergonomic exercises on modifying SIRT1 gene expression in obese Down syndrome patients. Forty obese Down syndrome patients (IQ level Ëƒ 60) were included in current study. Their age were ranged from 14 to 18 years old, their body mass index (BMI) was ranged from 30kg/m2 to 39.9 kg/ m2, These patients were divided randomly and equally into two groups GI composed of twenty obese patients with down syndrome. They were received indoor ergonomic exercises two times / week for 3 months plus balanced diet and GII composed of twenty obese patients with Down syndrome. They were received balanced diet only. Data were obtained from each patient for BMI and SIRT1 level. Measurements were performed before study and after three months. Statistical analysis revealed that there was reduction of BMI within both groups after treatment in comparison to pre-treatment (p
Keywords: Obesity, Down syndrome, Sirtuin 1, gene expression.